Bissu and Toboto Domain; Lanskap, Islam, dan Negosiasi - Feby Triadi (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2019)
This research found a dividing line between the narrative of Bissu and Toboto, in some previous research, they were always singularly narrated. But this Research looks at other phenomena of Bissu, namely Toboto, present and playing a role in their daily lives. That way, this article wants to reveal another narrative that has been supporting the Bissu as a single narrative. It also focused on landscapes, Islam and negotiations, using ethnographic methods, taking the context of research in Pangkep Regency and confirming the data, with Bissu and adat councils in Bone District, making this research conducted from November to December. The analytical technique used is structural-functional, which sees exchange relations between people who have their respective structures and functions. This research found several updates. First, the context in seeing Bissu daily life is always centered on Segeri Subdistrict, but what is in the field, it turns out Bissu residence is not only in Segeri District. Secondly, as far as any behavior deviates from the behavior of Bissu and Toboto, Islam as a religion teaching always returns them to their nature. And thirdly, negotiations between the two camps (adat council and religious leaders) are like a time bomb that is ready to explode at any time.